2019
DOI: 10.1038/s41598-019-42209-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Phenotypes Induced by Three Degrees of Transverse Aortic Constriction in Mice

Abstract: Transverse aortic constriction (TAC) is a well-established model of pressure overload-induced cardiac hypertrophy and failure in mice. The degree of constriction “tightness” dictates the TAC severity and is determined by the gauge (G) of needle used. Though many reports use the TAC model, few studies have directly compared the range of resulting phenotypes. In this study adult male mice were randomized to receive TAC surgery with varying degrees of tightness: mild (25G), moderate (26G) or severe (27G) for 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
88
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 38 publications
(46 reference statements)
5
88
1
Order By: Relevance
“…Pressure overload triggers the expression of inflammation genes. Inhibiting early inflammation reactions can reduce cardiac remodeling and improve heart function ( Suetomi et al, 2018 ; Richards et al, 2019 ). Fibrosis is a pivotal player in the development and progression of heart failure, which is controlled by the TGF-β/Smads pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Pressure overload triggers the expression of inflammation genes. Inhibiting early inflammation reactions can reduce cardiac remodeling and improve heart function ( Suetomi et al, 2018 ; Richards et al, 2019 ). Fibrosis is a pivotal player in the development and progression of heart failure, which is controlled by the TGF-β/Smads pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, Furihata et al found operation with a 0.400 mm gauge needle led to the state of hypertrophy without left ventricular dysfunction at 4 weeks after surgery, in which the authors also showed that the 0.385 mm and 0.375 mm group (smaller constriction diameter than that in our study) of mice represented efficient in left ventricular failure at 4 weeks, while the average bodyweight of mice (19‐26 g) in the research was lower than that in our study. In another study Richards et al reported that TAC mice using a 27 gauge blunt needle (smaller constriction diameter than 0.400 mm) developed significant cardiac dysfunction, however, the important point of note they found was the cardiac response to different degrees of constriction seemed not to be quite consistent with the severities of phenotype because the exacerbation of several cardiac parameters was not step‐wise such as fractional shortening, ejection fraction, left atrial area, etc These reports indicate the underlying mechanisms governing these distinct responses to TAC in murine heart under different degrees of insult are still not clear, which deserves further study to figure out the potential reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional color Doppler imaging was used to demonstrate laminar blood flow in the sham group and turbulent blood flow in the TAC group on the aortic arch. Pulsed-wave Doppler was used to measure the velocity of the blood flow in the aortic arch, and the pressure gradient in the arch was calculated using the modified Bernoulli equation (Pressure gradient = 4 × velocity 2 )[21].…”
mentioning
confidence: 99%